SARS-CoV-2 receptor a distinct genetic profile specific to the Iraqi Kurdish population: SARS-CoV-2 receptor genetic profile - Mustafa, Suhad Asaad (Cellular and Molecular Biology, 2024)
SARS-CoV-2, the virus responsible for COVID-19, enters host cells by binding its spike protein's receptor-binding domain (RBD) to the human angiotensin-converting enzyme 2 (ACE2) receptor's peptidase domain (PD). This interaction plays a crucial role in the virus's ability to invade host cells and establish infection. Numerous studies have identified specific residues crucial for their binding interaction. Our objective was to determine whether natural variations in the ACE2 receptor could impact its affinity for the S-protein RBD. To explore this, we focused on investigating the effects of natural variations in the ACE2 PD residues on its binding affinity to the S-protein RBD interface of SARS-CoV-2. We conducted a genotyping study in the Iraqi Kurdish population and identified significant genetic variations in key binding residues of the ACE2 PD residues, including N330K, K353R, R357Q, P389H, and R393H. These variations suggest a distinct genetic profile specific to the Kurdish population regarding their interaction with the SARS-CoV-2 virus. Understanding the implications of these variations is essential for comprehending the mechanisms of viral infection, developing targeted therapeutics, and refining treatment strategies and vaccine design. Additionally, studying these variations can provide insights into population-specific vulnerabilities, help monitor viral evolution and transmission, and guide the development of effective interventions.